Lowest Case Fatality Rate for Patients With Acute Pancreatitis Admitted in Gastroenterology Units in Veneto Region, Italy. Issue 9 (October 2019) - Cavallaro, Lucas Giovanni; Germanà, Bastianello; Venerito, Marino; Frulloni, Luca; Farinati, Fabio; Gabbrielli, Armando; Saia, Mario
Abstract : Objectives: This study aimed to evaluate trends in hospitalizations and outcomes of acute pancreatitis (AP) according to first admitting hospital unit and hospital volumes. Methods: Hospital discharge records of patients with AP admitted in the Veneto Region (Northeast Italy) during the period 2001–2015 were examined. Results: A total of 23, 389 patients (54% males; mean age, 62.2 years; standard deviation, 19.3 years) were admitted for AP. Both hospitalization (32.4 to 29.5/100, 000 inhabitants per year; P < 0.05) and in-hospital mortality (1.41 to 0.79/100, 000 inhabitants per year; P < 0.05) decreased over the study period. Case fatality rate was altogether 3.2%. The percentages of patients admitted in surgery, nongastroenterology medical units, gastroenterology, and intensive care were 52%, 30%, 16%, and 2%, respectively. Fewer fatalities were observed in gastroenterology units (1.7%) compared with nongastroenterology medical units (4.3%; odds ratio, 0.37; 95% confidence interval, 0.28–0.49) and surgical units (2.7%; odds ratio, 0.61; 95% confidence interval, 0.47–0.80). Fatalities decreased progressively with increasing hospital volumes from 3.7% to 2.9% ( P < 0.05). Conclusion: In the Veneto Region, both hospitalizations and in-hospital mortality for AP significantly decreased over the last 15 years. Case fatality rate was lowest for patients admitted in gastroenterology units.